Narrative, imagination and concepts of fiction in late antique hagiography - Pelt, Julie van; Temmerman, Koen de; Staat, Klazina (Mnemosyne <Leiden> / Supplementum, 2024)
"This volume explores concepts of fiction in late antique hagiographical narrative in different cultural and literary traditions. It includes Greek, Latin, Syriac, Armenian, Persian and Arabic material. Whereas scholarship in these texts has traditionally focussed on historical questions, this book approaches imaginative narrative as an inherent element of the genre of hagiography that deserves to be studied in its own right. The chapters explore narrative complexities related to fiction, such as invention, authentication, intertextuality, imagination and fictionality. Together, they represent an innovative exploration of how these concepts relate to hagiographical discourses of truth and the religious notion of belief, while paying due attention to the various factors and contexts that impact readers' responses"--